What Has Changed Since 2015? A New and Expanded Update on Copyright Practices and Approaches at Canadian Post-Secondaries - Graham, Rumi; Winter, Christina (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2021)
Objective – The aim of this study is to update our understanding of how Canadian post-secondary institutions address copyright education, management, and policy matters since our last survey conducted in 2015. Through the new survey, we seek to shed further light on what is known about post-secondary educational copying and contribute to filling some knowledge gaps such as those identified in the 2017 statutory review of the Canadian Copyright Act.Methods – In early 2020, a survey invitation was sent to the person or office responsible for oversight of copyright matters at member institutions of five Canadian regional academic library consortia. The study methods used were largely the same as those employed in our 2015 survey on copyright practices of Canadian universities.Results – In 2020, respondents were fewer in number but represented a wider variety of types of post-secondary institutions. In general, responsibility for copyright services and management decisions seemed to be concentrated in the library or copyright office. Topics covered and methods used in copyright education remained relatively unchanged, as did issues addressed in copyright policies. Areas reflecting some changes included blanket collective licensing, the extent of executive responsibility for copyright, and approaches to copyright education. At most participating institutions, fewer than two staff were involved in copyright services and library licenses were the permissions source most frequently relied on “very often.” Few responded to questions on the use of specialized permissions management tools and compliance monitoring.Conclusion – Copyright practices and policies at post-secondary institutions will continue to evolve and respond to changes in case law, legislation, pedagogical approaches, and students’ learning needs. The recent Supreme Court of Canada ruling on approved copying tariffs and fair dealing provides some clarity to educational institutions regarding options for managing copyright obligations and reaffirms the importance of user’s rights in maintaining a proper balance between public and private interests in Canadian copyright law.